Antioxidant Potential of Seed Extracts of Cucurbita Pepo, Ocimum Basillicum, Trachyspermum Ammi and Linum Usitatissimum - Individual and Synergistic Effect - Subbiah, Shanthi; Kannasandra Ramaiah, Manjula; G. Singh, Kavitha (Journal of Neonatal Surgery, 2025)
The plant kingdom is known for its rich antioxidant compounds. They have shown promise not just as food additives that prevent oxidation but also as supplements that prevent diseases brought on by oxidative stress. Antioxidants are rich in phytochemicals like flavonoids, carotenoids, polyphenolics and can readily scavenge free radicals. The present study aimed at screening phytoconstituents like terpenoids, alkaloids, saponins, tannins, flavonoids, phenolics and antioxidant potential in seed extracts of Cucurbita pepo (pumpkin), Ocimum basillicum (Basil), Trachyspermum ammi (Ajwain) and Linum usitatissimum (flax) in three different solvents. The extensive study investigated the synergistic antioxidant potential of methanolic, aqueous, and ethyl acetate extracts of the selected 4 seeds in comparison with individual seed extracts. ABTS (2,2’-azino-bis(3-ethylbenzothiazoline-6 sulfonic acid assay) studied the antioxidant effect. The variance in IC 50 values between solvents reveals the polarity of the solvents, as well as the polarity of the extracted phytochemicals which may affect how much phytochemical extraction is accomplished. ABTS assay measures radical scavenging capacity in terms of absorbance. The result findings were expressed as percentage inhibition in three different solvents – methanolic extracts ranging from 48.35±0.55 to 93.24±0.35; aqueous extract 49.27±0.06 to 89.63±0.05; ethyl acetate extract 52.32±0.67 to 95.66±0.04. The results established that synergistic IC50 values are significantly lesser indicating higher antioxidant potential than individual seed extracts in all three chosen solvents. The benefits of these seed extracts’ synergistic antioxidant properties can be investigated in further detail, for their potential applications as natural preservatives in cooking oils and supplements in food products to enhance immunity and prevent chronic diseases caused by oxidative stress.